The Role of Teachers in Enhancing Student Learning Interest at SDN 1 Samadua - aida rosni (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Student interest in learning is a crucial indicator of educational success. Teachers play a central role in creating a conducive and engaging learning environment. This study aims to identify the role of teachers in enhancing students' learning interest at SDN 1 Samadua, Aceh Selatan. A qualitative approach was employed in this research, utilizing methods such as observation, in-depth interviews, and document studies. The research subjects included teachers, students, and parents. The findings indicate that teachers at SDN 1 Samadua employ various strategies, such as personal approaches, project-based learning methods, and the integration of simple technology in the teaching and learning process. Challenges faced include limited facilities and support from students' families. These findings emphasize the importance of ongoing training for teachers and support from both the school and family to maximize students' learning interest